2019
DOI: 10.1029/2018jd029892
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Laboratory and Ambient Biomass Burning Aerosols: Elucidating Black, Brown, and Organic Carbon Components and Mixing Regimes

Abstract: Biomass burning (BB) is an important global source of aerosol and trace gases that degrade air quality, decrease visibility, and impact climate and human health. Refractory black carbon (rBC), brown carbon (BrC), and organic aerosol are major components of BB emissions. BB aerosol composition is highly variable at the source and depends on fuel composition and combustion phase. Atmospheric aging alters fresh BB aerosol through processes that are complex and dynamic. To better understand the variability in opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 127 publications
(265 reference statements)
3
24
0
Order By: Relevance
“…This remains true even if we change the real part of refractive index of BC to 1.7 (Figure c) or change the imaginary part to 0.3 (Figure d), or if we adopt the refractive index of 1.95–0.79i. Thus, in agreement with earlier publications (Lack & Cappa, ; Romonosky et al, ; Zhang et al, ), and rounding to the higher one decimal place number, we conclude that the AAE(405/781) of a mixture of BC and spectrally flat organic material is limited by AAEitalicBCitalicOC()4057811.7. …”
Section: Bc‐oc In Internal Mixturesupporting
confidence: 93%
See 4 more Smart Citations
“…This remains true even if we change the real part of refractive index of BC to 1.7 (Figure c) or change the imaginary part to 0.3 (Figure d), or if we adopt the refractive index of 1.95–0.79i. Thus, in agreement with earlier publications (Lack & Cappa, ; Romonosky et al, ; Zhang et al, ), and rounding to the higher one decimal place number, we conclude that the AAE(405/781) of a mixture of BC and spectrally flat organic material is limited by AAEitalicBCitalicOC()4057811.7. …”
Section: Bc‐oc In Internal Mixturesupporting
confidence: 93%
“…This provides an opportunity to estimate the imaginary part of the refractive index (assuming that the real part is known) of BC from the maximum SSA value (Figure b). For example, the samples used in laboratory measurements by Romonosky et al () and shown in their Figures and , suggest by comparison with our Figure , the imaginary part of the refractive index close to 0.5i for BC, and close to 0.2i for nigrosin.…”
Section: Bc and Aaesupporting
confidence: 83%
See 3 more Smart Citations